2022
DOI: 10.1097/rli.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Combining Deep Learning and Radiomics for Automated, Objective, Comprehensive Bone Marrow Characterization From Whole-Body MRI

Abstract: Objectives: Disseminated bone marrow (BM) involvement is frequent in multiple myeloma (MM). Whole-body magnetic resonance imaging (wb-MRI) enables to evaluate the whole BM. Reading of such whole-body scans is time-consuming, and yet radiologists can transfer only a small fraction of the information of the imaging data set to the report. This limits the influence that imaging can have on clinical decision-making and in research toward precision oncology. The objective of this feasibility study was to implement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…13 Few studies have applied radiomics to analyze MRIs from multiple myeloma patients so far. [39][40][41][42] Knowledge on robust RFs in multiple myeloma could be of use to reduce the RF set before modeling, especially given the limited cohort sizes of these studies, and help to improve the robustness of radiomics models for multicentric application.…”
Section: Reproducibility Of Radiomics Features Under Variation Of Mri...mentioning
confidence: 99%
“…13 Few studies have applied radiomics to analyze MRIs from multiple myeloma patients so far. [39][40][41][42] Knowledge on robust RFs in multiple myeloma could be of use to reduce the RF set before modeling, especially given the limited cohort sizes of these studies, and help to improve the robustness of radiomics models for multicentric application.…”
Section: Reproducibility Of Radiomics Features Under Variation Of Mri...mentioning
confidence: 99%
“…It produced segmentations with mean dice scores of 0.92 and 0.93 for the pelvic bones and 0.85 for the sacral bone, which were even higher than the dice scores of the interrater experiments that were performed to set a benchmark. The dice scores of the ADC-nnU-Net are similar to the dice scores for bone marrow segmentation from T1-weighted wb-MRI images from 1 prior study 28 and markedly higher than the dice scores for bone segmentation from another wb-MRI study that reported dice scores of 0.76 for the best achieved algorithm 37 . The quality for the segmentation of the sacral bone was lower than the quality for the segmentation of the pelvic bones, which is in line with the lower interrater reproducibility of the sacrum in this study, and is also in line with findings from automatic bone marrow segmentations on T1-weighted images 28 .…”
Section: Discussionmentioning
confidence: 56%
“…The dice scores of the ADC-nnU-Net are similar to the dice scores for bone marrow segmentation from T1-weighted wb-MRI images from 1 prior study 28 and markedly higher than the dice scores for bone segmentation from another wb-MRI study that reported dice scores of 0.76 for the best achieved algorithm 37 . The quality for the segmentation of the sacral bone was lower than the quality for the segmentation of the pelvic bones, which is in line with the lower interrater reproducibility of the sacrum in this study, and is also in line with findings from automatic bone marrow segmentations on T1-weighted images 28 . The quality for the segmentation was lower in data set 3 from center 3, which can be explained by the fact that the nnU-Net was trained on data from center 1 and 2, and therefore performed better on data from these scanners.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…While there are methods to control for the influence of rater variability from the segmentations [45,46], the usage of automatic segmentations is often considered better as the transfer to other clinical settings is more straightforward [47]. While there are some studies that make use of automatic segmentations [48,49], this is not always true. We assume that the comparatively small size of many studies [16,50,51] hinders the researcher in investing additional efforts.…”
Section: Discussionmentioning
confidence: 99%